Field observations of Ateleia glazioviana poisoning in cattle in southern Brazil - Gava A.* (2001)
Ateleia glazioviana is an important poisonous plant from southern Brazil. Heavy losses in cattle from this region occur each year due to ingestion of the plant. The epidemiological, clinical, gross and histopathological features of A glazioviana poisoning in cattle are described here from a 5-year field survey in southern Brazil. A glazioviana poisoning in cattle induces 3 clinical presentations: abortions, disease characterized by lethargy, and cardiac failure. The latter is associated with marked necrosis and fibrosis of the myocardium and can cause sudden death or congestive heart failure.